2007
DOI: 10.1093/jxb/erm102
|View full text |Cite
|
Sign up to set email alerts
|

Lotus tenuis tolerates the interactive effects of salinity and waterlogging by 'excluding' Na+ and Cl- from the xylem

Abstract: Salinity and waterlogging interact to reduce growth of poorly adapted species by, amongst other processes, increasing the rate of Na(+) and Cl(-) transport to shoots. Xylem concentrations of these ions were measured in sap collected using xylem-feeding spittlebugs (Philaenus spumarius) from Lotus tenuis and Lotus corniculatus in saline (NaCl) and anoxic (stagnant) treatments. In aerated NaCl solution (200 mM), L. corniculatus had 50% higher Cl(-) concentrations in the xylem and shoot compared with L. tenuis, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
67
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(73 citation statements)
references
References 59 publications
6
67
0
Order By: Relevance
“…Several regulation mechanisms can explain the lower ion concentration in leaves at an intermediate salinity level. First, relatively little Na + and Cl − are probably transported from the roots to the shoot-a mechanism already documented in Sorghum and Lotus tenuis (De Lacerda et al 2003;Teakle et al 2007). Second, recirculation of Na + and Cl − in the phloem is also a possibility (Munns 2002;Teakle et al 2007).…”
Section: Water Statusmentioning
confidence: 92%
See 1 more Smart Citation
“…Several regulation mechanisms can explain the lower ion concentration in leaves at an intermediate salinity level. First, relatively little Na + and Cl − are probably transported from the roots to the shoot-a mechanism already documented in Sorghum and Lotus tenuis (De Lacerda et al 2003;Teakle et al 2007). Second, recirculation of Na + and Cl − in the phloem is also a possibility (Munns 2002;Teakle et al 2007).…”
Section: Water Statusmentioning
confidence: 92%
“…First, relatively little Na + and Cl − are probably transported from the roots to the shoot-a mechanism already documented in Sorghum and Lotus tenuis (De Lacerda et al 2003;Teakle et al 2007). Second, recirculation of Na + and Cl − in the phloem is also a possibility (Munns 2002;Teakle et al 2007). Medina et al (2007; showed that, in P. officinalis leaves, Na + concentration is low (2-27 mmol kg −1 of dry weight) and the K/Na ratio is high (between 70 and 205), coming to the conclusion that the shoot has a large exclusion capacity regarding Na + .…”
Section: Water Statusmentioning
confidence: 92%
“…Excessive chloride ion (Cl -) accumulation in the cytoplasm of plant cells, particularly in the shoot, is also toxic to plants (Tyerman, 1992;Xu et al, 1999;Munns and Tester, 2008;Teakle and Tyerman, 2010;Geilfus et al, 2015), resulting in a reduction in plant growth and symptoms such as leaf burn and leaf abscission for Cl --sensitive species (Abel, 1969;Parker et al, 1983;Cole, 1985). Cl -, rather than sodium ions (Na + ), is considered to be the more toxic ion for woody perennial species such as grapevine (Vitis vinifera; Tregeagle et al, 2006;Gong et al, 2011) and citrus (Citrus jambhiri; Storey and Walker, 1999) and legumes such as soybean (Glycine max; Luo et al, 2005) and lotus (Lotus tenuis; Teakle et al, 2007). For cereal crops such as wheat (Triticum aestivum; Martin and Koebner, 1995) and barley (Hordeum vulgare; Tavakkoli et al, 2011), the toxic effects of Cl -and Na + are additive and can often be overcome by restricting excess accumulation of both ions in the shoot.…”
mentioning
confidence: 99%
“…For cereal crops such as wheat (Triticum aestivum; Martin and Koebner, 1995) and barley (Hordeum vulgare; Tavakkoli et al, 2011), the toxic effects of Cl -and Na + are additive and can often be overcome by restricting excess accumulation of both ions in the shoot. It has also been shown that the xylemsap Cl -content of salt-tolerant genotypes of wheat (Läuchli et al, 2008), citrus (Moya et al, 2003), and lotus (Teakle et al, 2007) is lower when compared with salt sensitive genotypes, suggesting that the control of Cl -concentration in the transpiration stream is a contributing factor to plant salinity tolerance. However, the molecular determinants of long-distance Cl -transport in plants and how it is regulated in response to salinity stress are still largely unknown (Teakle and Tyerman, 2010;Henderson et al, 2014).…”
mentioning
confidence: 99%
“…There is a difference in response to salinity between soil and solution culture studies. Capacity to control Cl − exclusion from shoots has been correlated with salt tolerance in many species of plants (Teakle et al 2007;Teakle and Tyerman 2009). …”
Section: Chloride Toxicitymentioning
confidence: 99%